2015
DOI: 10.1128/jcm.01611-14
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Mycobacterial Interspersed Repetitive-Unit–Variable-Number Tandem-Repeat Genotyping for Mycobacterium tuberculosis Epidemiological Studies

Abstract: dThe emergence of drug-resistant forms of tuberculosis (TB) represents a major public health concern. Understanding the transmission routes of the disease is a key factor for its control and for the implementation of efficient interventions. Mycobacterial interspersed repetitive-unit-variable-number tandem-repeat (MIRU-VNTR) marker typing is a well-described method for lineage identification and transmission tracking. However, the conventional manual genotyping technique is cumbersome and time-consuming and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…It would increase accuracy to 99.63% in Albania and 99.19% in Tunisia with a very high overall rate of concordance of 99.41%. These results are in line with other studies performed so far on MIRU-VNTR typing of MTBC with the QIAxcel system [14,15].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It would increase accuracy to 99.63% in Albania and 99.19% in Tunisia with a very high overall rate of concordance of 99.41%. These results are in line with other studies performed so far on MIRU-VNTR typing of MTBC with the QIAxcel system [14,15].…”
Section: Discussionsupporting
confidence: 93%
“…The QIAxcel system is an accurate method that detects allele lengths with a precision of 5 bp in more than half of the cases. For a proper allele calling, the maximum sizing deviation must not exceed half of the shortest repeat length [15]. Sizing deviation did not exceed 20 bp in Tunisia.…”
Section: Discussionmentioning
confidence: 97%
“…tuberculosis isolates using 15- and 24 loci standard VNTR panels, overall concordance rate with the reference method was 98.9% demonstrating potential suitability of the system for routine M . tuberculosis genotyping [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of this study was to determine the reproducibility of 15-loci MIRU-VNTR method in different clinical samples isolated from confirmed patients. The DNA was extracted from the M. tuberculosis isolates by the boiling technique using 15 primers for MIRU-VNTR and PCR protocols has been used according to Gauthier et al (3). The PCR product was detected by the 1.5% agarose gel electrophoresis and the copy number of each repeated allele was determined in comparison with the H37RV PCR product as the standard strain.…”
Section: Objectivesmentioning
confidence: 99%
“…Supply et al in the first paper published for the introduction of automated MIRU-VNTR method stated that 12-loci MIRU-VNTR typing was 100% reproducible, as all blinded duplicate samples analyzed were correctly assigned; they showed a small variation in the amplicon size of each locus in different repetitions (2). Gauthier et al confirmed the repeatability and reproducibility of the automated MIRU-VNTR method (3). None of these studies assessed the MIRU-VNTR reproducibility among different M. tuberculosis isolates taken from the same patient on different days or different clinical samples.…”
Section: Introductionmentioning
confidence: 98%